Menyusun Jejak Sukses: Tantangan Dan Solusi Dalam Penerapan Konsep Komunikasi Organisasi Di RSAU Dr. Sukirman Lanud Roesmin Nurjadin - Fitra, Rosi Deli; Hartono, Budi (Komunika : Jurnal Ilmiah Komunikasi, 2024)
The implementation of Organizational Communication is a critical component in improving the efficiency, effectiveness, and quality of health services to military personnel and the community. However, this process is often faced with various complex challenges, which can affect the effectiveness and success of implementation. This paper analyzes the various problems that are often faced in the implementation of Organizational Communication in the workplace environment. Factors such as changes in the business environment, lack of resources, internal organizational dynamics, and lack of stakeholder involvement can hinder the successful implementation of Organizational Communication. In facing these challenges, several strategic solutions are proposed to facilitate a more effective and sustainable implementation of the Organizational Communication concept. By focusing on cross-departmental collaboration, in-depth analysis of market trends, intelligent resource management, and an inclusive approach to stakeholder involvement, RSAU dr. Sukirman Lanud Roesmin Nurjadin can overcome existing obstacles and increase the chances of achieving the implementation of the Organizational Communication concept. By combining the right approach and creativity in dealing with the complexity of the health environment, especially in today's military health organizations, RSAU dr. Sukirman Lanud Roesmin Nurjadin can build a strong and sustainable track record of success in implementing the Organizational Communicationconcept.